2010
DOI: 10.1021/la904238n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Etching on the Efficiency of ZnO-Based Dye-Sensitized Solar Cells

Abstract: In this study, we report on an insight into the influential factors of the conversion efficiency of ZnO-based dye-sensitized solar cells. With ZnO nanoflowers as the photoelectric anode and dye N719 as the sensitizer, we found with the addition of N719 that the surfaces of ZnO nanoflowers were slightly etched at the beginning and gradually destroyed with time. On the basis of these observations, a series of experiments were further carried out to distinguish the influence of dye-induced aggregation from that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 22 publications
1
45
1
Order By: Relevance
“…Dye aggregation leads to slower electron injection and higher charge recombination [36,37]. The end result is a lower J SC and overall conversion efficiency [39]. These reports support the trends of τ eff and J SC versus dye adsorption time observed in this study.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Dye aggregation leads to slower electron injection and higher charge recombination [36,37]. The end result is a lower J SC and overall conversion efficiency [39]. These reports support the trends of τ eff and J SC versus dye adsorption time observed in this study.…”
Section: Resultssupporting
confidence: 82%
“…For example, when a dye adsorption time of 3 h (optimal for the 31-μm film) was applied to the 20-μm film, the conversion efficiency dropped from the peak value of 4.95% to approximately 3.4%, representing a 31% drop. Prolonged dye adsorption times cause dye aggregation [32,35-38] and etching of the ZnO surface [39], both of which result in performance deterioration in ZnO-based DSSCs. Conversely, TiO 2 -based DSSCs are typically less sensitive to prolonged sensitization times because of the higher chemical stability of TiO 2 [32-34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ZnO is etched by N719 dye molecules resulting in deterioration of DSCs [25]. Although Diamant et al said that basic coating layers shift conduction band in negative direction [26], a direct proof that present conduction band shift by coating layers was not shown in this study.…”
Section: Inorganic Surface Passivation Of Tio 2 Nanotube Arrays For Dscscontrasting
confidence: 57%
“…Significantly, the high-electron mobility (~130e200 cm 2 V À1 s À1 ) and direct conduction path of vertical ZnO arrays would benefit electron transport with less recombination and enable the possibility for a larger open circuit voltage (V oc ) [23,26]. Further, ZnO has similar band gap (~3.2 eV) in comparison with TiO 2 [27]. Hence, vertical aligned ZnO arrays has been explored as electrodes in sensitized solar cells with great potential.…”
Section: Introductionmentioning
confidence: 99%